A Medaka Gene Map: The Trace of Ancestral Vertebrate Proto-Chromosomes Revealed by Comparative Gene Mapping - Naruse, Kiyoshi; Tanaka, Minoru; Mita, Kazuei; Shima, Akihiro; Postlethwait, John; Mitani, Hiroshi (Genome Research, 2004)
The mapping of Hox clusters and many duplicated genes in zebrafish indicated an extra whole-genome duplication in ray-fined fish. However, to reconstruct the preduplication chromosomes (proto-chromosomes), the comparative genomic studies of more distantly related teleosts are essential. Medaka and zebrafish are ideal for this purpose, because their lineages separated from their last common ancestor ∼140 million years ago. To reconstruct ancient vertebrate chromosomes, including the chromosomes of the vertebrate ancestor of humans from 450 million years ago, we mapped 818 genes and expressed sequence tags (ESTs) on a single meiotic backcross panel obtained from inbred strains of the medaka, Oryzias latipes. Comparisons of linkage relationships of orthologous genes among three species of vertebrates (medaka, zebrafish, and human) indicate the number and content of the chromosomes of the last common ancestor of ray-fined fish and lobe-fined fish (including humans), and the extra whole genome duplication event in the ray-fin lineage occurred in the common ancestor of perhaps all teleosts.
10.1101/gr.2004004